A peptide profile of amniotic fluid in a fetal lamb model of gastroschisis. Issue 3 (2014) - Ohyama, Kei; Sato, Toshiyuki; Tanaka, Kunihide; Manabe, Shutaro; Nagae, Hideki; Arito, Mitsumi; Iizuka, Nobuko; Kojima, Shigeki; Omoteyama, Kazuki; Seki, Yasuji; Kurokawa, Manae S.; Suematsu, Naoya; et al.
No abstract available